Variety Of Bhenga And Manu Ornaments At The Sa'o Traditional House Of Gurusina Traditional Village - Azizy, Irfan Maulana; Wimansyah, Yogasmara Binsar Putra; Sitinjak, Zhalzhabela Nur’aini; Indrayana, I Made Heri (Institut Seni Indonesia Denpasar, 2024)
East Nusa Tenggara (NTT) has a rich culture and diverse traditions. Several ethnic sub-groups, including the Ngada-Lio ethnic sub-group, mark this diversity. This ethnic sub-group inhabits the Ngada Regency area, where traditional villages are scattered at several points. Traditional villages are places to preserve a culture that has been passed down from generation to generation, one of which is weti carvings. These carvings have a variety of figures, including Bhénga and Manu. The depiction of these two figures is like a buffalo horn and a chicken. In some traditional houses in Indonesia, there are also similar figures, namely in the Tongkonan Toraja traditional house and the Karo Batak traditional house. This research is a qualitative descriptive research. The researcher chose this method to describe the figures of Bhéngaand Manu in detail and depth. This research began with observation and interviews, after which the research continued by analyzing the data using morphological, stylistic, and comparative analysis. The results of this study show that various ornamental figures of buffalo and chicken are depicted on the walls of the Sao traditional house because the two animals have a special closeness to the community. Besides that, the ornamental variety is carved on the wall of the traditional house as an addition to the aesthetic value of the traditional house.